BESARAN PERUSAHAAN, PROFITABILITAS, DIVIDEND PAYOUT RATIO, LEVERAGE OPERASI DAN WINNER/LOSSER STOCK TERHADAP PERATAAN LABA DI BURSA EFEK INDONESIA - RIZKA RAMAYANTI (Media Bisnis, 2014)
The Research was designed to provide the empirical evidence about income smoothing at on manufacturing companies listed in Indonesia Stock Exchange (IDX) and eximine five variables which were hypothesized influence income smoothing practices, they are company size, profitability, dividend payout ratio, Operating Leverage and Winner /Losser Stock. Eckel index was used to identify smoother and non smoother companies. Statistical analysis were used to examine hypothesies is logistic regression. Results of Eckel Index computation show that income smoothing was applies by manufaktur companies in Indonesia. In addition, result of analysis on the five variables which were hypothesized to influence the income smoothing show that Profitability was influence income smoothing practices. In addition, company size, Dividend Payout Ratio, Operating Leverage and Winner/Losser Stock were influence income smoothing practices.